THE EFFECT OF COMPANY SIZE AND LIQUIDITY ON CORPORATE SOCIAL RESPONSBILITY (CSR) THROUGH PROFIT AS AN INTERVENING VARIABLE IN SHARIA COMMERCIAL BANKS - Muhammad Chairiansyah Lubis; Muhammad Yafiz (SEAN Institute, 2023)
This study aims to determine the effect of company size (size) and liquidity on corporate social responsibility (CSR) through earnings as an intervening variable in Islamic commercial banks. This type of research is quantitative research with secondary data sources used. This study uses data from the annual financial reports of Islamic commercial banks for 2017-2021. The research sample is Islamic Commercial Banks in Indonesia in 2017-2021. The sample was selected using a purposive sampling technique in order to obtain eight Islamic Commercial Banks. Processing techniques and data analysis using Descriptive Statistical Analysis, Multiple Linear Regression Analysis, Classical Assumption Test and Hypothesis Test. The program used for calculations uses SPSS version 25 which then interprets the results from SPSS. The results of the study show that the variables of firm size and liquidity of Islamic banks have a significant effect on financial performance. Variable company size through corporate social responsibility has a significant effect on profits while the variable liquidity through corporate social responsibility has no significant effect